Сommunicative-functional Potential of Time as a Synergistic Vector of a Literary Work: Array - Oleinikova, Galina (Journal of Danubian Studies and Research, 2021)
Developing in the second half of the 20thcentury interdisciplinary scientific discipline synergetics has become a powerful methodological tool for research in the humanities associated with the study of society, culture, which are complex, self-organizing systems.Synergetics attracts the attention of researchers in the field of linguistics, the subject of study of which is language in all its diversity and complexity.The interest of linguists to the study of language functioning from the standpoint of synergetic methodology is due primarily to the fact that "the synergetic approach to the study of changing in language at different levels of its organization and forces a fresh look at some fundamental concepts, which have already become traditional"(Abakumov, 2013), which includes one of the important grammatical categories - the category of time.